At the Borders of Translation: Traditional and Modern(ist) Adaptations, East and West - Chan, Tak-Hung (Meta, 2009)
AbstractAdaptation, as both a method and a textual category, has been a perennial favorite with text mediators who call themselves translators, appearing especially prominently in intersemiotic rather than interlingual translation. The present paper examines the concepts and practices of adaptation, drawing particular attention to examples from both the West and the Far East. Just as a preference for adaptive methods in translation can be seen in certain periods of Western literary history (e.g. seventeenth- and eighteenth-century France), there were times when adaptations were hailed in China, Japan and Korea. In the course of the discussion, reference will be made to (1) the modernist adaptations undertaken by Western writers through much of the twentieth century; (2) the sequences of novelistic adaptations spawned in Korea and Japan by Chinese classical novels; and (3) the adaptations of European novels by the prodigious twentieth-century Chinese translator Lin Shu. It will be shown that there is a need for translation scholars to question the theoretical validity of the dichotomy between the two modes of “translation” and “adaptation,” as well as an urgency to reconsider the supposed “inferior” status of adaptations.